Powering a learning society during an age of disruption - Ra, Sungsup; Jagannathan, Shanti; Maclean, Rupert (Education in the Asia-Pacific Region: Issues, Concerns and Prospects, 2021)
This open access book presents contemporary perspectives on the role of a learning society from the lens of leading practitioners, experts from universities, governments, and industry leaders. The think pieces argue for a learning society as a major driver of change with far-reaching influence on learning to serve the needs of economies and societies. The book is a testimonial to the importance of learning communities. It highlights the pivotal role that can be played by nontraditional actors such as city and urban planners, citizens, transport professionals, and technology companies. This collection seeks to contribute to the discourse on strengthening the fabric of a learning society crucial for future economic and social development, particularly in the aftermath of the coronavirus disease.